Determinants of Early Childhood Health and Nutrition: an Evidence-Based Integrative Study to Strengthen Holistic Integrative Preschool Services in Soppeng District - Mutmainnah; Aisyah; Nurfadillah; Nurfiani; Giska Aruni; Arviani Susandi; Rohana Ibrahim; Maswati (Journal of Creative Power and Ambition (JCPA), 2026)
Early childhood health and nutrition are the primary foundations for developing quality human resources, directly determining children's cognitive, physical, socio-emotional development capacity, and future productivity. This study aims to analyze the multidimensional determinants of early childhood health and nutrition, identify the current nutritional status and influencing factors, and examine the implementation and effectiveness of the Holistic Integrative Early Childhood Education (PAUD Holistik Integratif) approach in improving children's health and nutrition at Posyandu Apel, Pising Village, Donri-Donri District, Soppeng Regency. The research employed a qualitative descriptive approach adopting evidence-based integrative review principles, combining field data with comprehensive scientific literature analysis. Data were collected through participant observation, semi-structured in-depth interviews, and documentation during Posyandu activities, with thematic analysis involving source triangulation to ensure validity. Results show that most children have normal nutritional status based on BB/U and BB/TB indicators, but cases of undernutrition and stunting requiring serious attention were still found. Five key determinants identified include: (1) individual factors (low birth weight history and disease history); (2) family factors (parental nutrition knowledge and socioeconomic conditions); (3) environmental factors (sanitation and clean water access); (4) behavioral factors (dietary patterns and clean healthy behavior); and (5) service access factors (Posyandu participation and PAUD involvement). The Holistic Integrative PAUD approach proved relevant in integrating health, nutrition, education, and parenting services, but still faces challenges in cross-sector coordination, resource limitations, and uneven community participation. The study concludes that strengthening multisectoral synergy among families, Posyandu, PAUD institutions, and village government is the key strategy for stunting prevention and sustainable optimization of early childhood development.